IMPLEMENTATION OF A REHABILITATION PROGRAM: INTERVENTION OF THE REHABILITATION SPECIALIST NURSE IN AN ICU - Maria De Fátima Alves Pereira Ferreira; Maria Rosário Peres (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Introduction: Early mobilization in critical patients as been considered as an intervention capable of decreasing morbidity risk factors and functional decline. Objectives: Evaluate safety of a rehabilitation program in a Portuguese Intensive care unit (ICU); evaluate if it has an early beginning; evaluate if critical patients did the sit/stand-up position early and identify the strength gains. Methods: A quantitative descriptive study was performed. The data was analysed with Microsoft Excel and Tableau 10.1 software. The sample was composed of 146 critical patients of both genders, submitted to 800 sessions of a rehabilitation program. Results: The average age of the patients was situated at 63,9 years with an average hospitalization length of 20,6 days; 7,25% experienced adverse events and 8,5% suffered motor complications; 56,62% started the rehabilitation program in the first 72 hours; 25% of the rehabilitation sessions resulted in sit/stand-up position and average strength gains from 0,364 strength degrees, for the lowest performing group analysed, to a maximum of 2,6 strength degrees in the group that revealed the best results. Conclusion: The results revealed an early and safe implementation of the rehabilitation program, resulting in health gains to critical patients. However, data relative to the timing of the fulfilment of the sit/stand-up position in critically ill patients is inconclusive.